2011
DOI: 10.1021/ac201466m
|View full text |Cite
|
Sign up to set email alerts
|

Designing Electrochemical Interfaces with Functionalized Magnetic Nanoparticles and Wrapped Carbon Nanotubes as Platforms for the Construction of High-Performance Bienzyme Biosensors

Abstract: The design of a novel biosensing electrode surface, combining the advantages of magnetic ferrite nanoparticles (MNPs) functionalized with glutaraldehyde (GA) and poly(diallyldimethylammonium chloride) (PDDA)-coated multiwalled carbon nanotubes (MWCNTs) as platforms for the construction of high-performance multienzyme biosensors, is reported in this work. Before the immobilization of enzymes, GA-MNP/PDDA/MWCNT composites were prepared by wrapping of carboxylated MWCNTs with positively charged PDDA and interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 36 publications
(62 reference statements)
0
31
0
Order By: Relevance
“…PDDA is a water soluble, quaternary ammonium cationic polyelectrolyte. It is positively charged colloid when dissolved in aqueous solutions [31,32]. The positively charged PDDA polymer can be easily wrapped/coated on negatively charged MWCNTs [33].…”
Section: Preparation Of Enzyme Modified Screen Printed Electrodementioning
confidence: 99%
“…PDDA is a water soluble, quaternary ammonium cationic polyelectrolyte. It is positively charged colloid when dissolved in aqueous solutions [31,32]. The positively charged PDDA polymer can be easily wrapped/coated on negatively charged MWCNTs [33].…”
Section: Preparation Of Enzyme Modified Screen Printed Electrodementioning
confidence: 99%
“…Luo et al [40] have demonstrated an effective ICP-MS-based multiplex and ultrasensitive assay of viruses with lanthanide-coded oligonucleotide hybridization and rolling circle amplification (RCA) strategies on biofunctional magnetic nanoparticles (MNPs) (Figure 1(b)). Single-stranded capture DNAfunctionalized MNPs were used for the separation of target [39]; (b) ICP-MS-based multiplex DNA assay with lanthanide-coded oligonucleotide hybridization strategy and biofunctional magnetic nanoparticle (MNP) enrichment [40]; (c) the sandwich DNA hybridization assay and the experimental procedure for the detection of target ssDNA strands using a SERS liquid chip (SLC) method [47]; (d) steps involved in the construction and function of the HRP/ChO x /GA-MNP/PDDA/MWCNT/GCE biosensor [53].…”
Section: Virusmentioning
confidence: 99%
“…Eguilaz et al [53] have designed a novel biosensing electrode surface that combines the advantages of magnetic ferrite nanoparticles functionalized with glutaraldehyde (GA) and poly(diallyldimethylammonium chloride) (PDDA)-coated multiwalled carbon nanotubes (MWCNTs) as platforms for the construction of high-performance multienzyme biosensors (Figure 1(d)). A detection limit of 0.85 µmol/L for cholesterol was achieved, which was advantageously compared with the analytical characteristics of other CNT-based cholesterol biosensors.…”
Section: Small Moleculesmentioning
confidence: 99%
“…PDDA-MWCNTs-GR hybrid was prepared according to the literatures with minor modifications [33,43]. 2 mg of MWCNTs and GR (3:1, MWCNTs:GR) were dispersed into 4 ml of 0.25% PDDA aqueous solution (containing 0.5 M NaCl) by sonication.…”
Section: Preparation Of Pdda-mwcnts-gr Hybridmentioning
confidence: 99%